Evaluation of riboflavin photochemical treatment for inactivation of HCT116 tumor cells mixed in simulative intraoperative salvage blood. Issue 10 (30th September 2019) - Yu, Yang; Yang, Lu; He, Chunyu; Tai, Shengfei; Ma, Chunya; Yang, Tianxin; Wang, Deqing
Abstract : BACKGROUND: Radiation and filtration have achieved satisfactory results in inactivation or removal of tumor cells mixed in salvage blood, but some drawbacks remain. This study evaluated the inactivation on HCT116 cells mixed in simulative salvage blood by riboflavin photochemical treatment. METHODS: HCT116 cells were added to the whole blood to simulate contaminated salvaged blood. The mixed blood was added with riboflavin of 50 μmol/L final concentration and illuminated by ultraviolet light. The samples were divided into control group and Experimental Groups 1 (18 J/cm 2 ), 2 (23.4 J/cm 2 ), and 3 (28.8 J/cm 2 ). An autotransfusion system (Cell Saver Elite, Haemonetics) was used to simulate the intraoperative blood salvage procedure to deal with whole blood. The apoptosis rate and tumorigenicity of HCT116 cells and the superimposed damage to red blood cells (RBCs) were evaluated. RESULTS: The apoptosis rates of HCT116 in Experimental Groups 1, 2, and 3 were much higher than that in the control group. Tumor growth was found in the control group, but no tumor growth was found in the three experimental groups. The hemolysis rates in the three experimental groups were significantly higher than that in the control group, but much lower than the quality standard of RBCs at the end of preservation. The concentration of adenosine triphosphate in RBCs was comparable in the control and experimental groups. CONCLUSION: Riboflavin at a 50 μmol/L final concentration and 18 J/cm 2 ultraviolet illumination can effectively inactivate HCT116 cells in salvaged blood, with minimum damage to the structure and function of RBCs, and the main quality indexes of salvaged RBCs were within the standard range.